The effects of concept mapping as a cognitive strategy in reading comprehension lessons: an experimental study on a group of BEL 250 students of UiTM Terengganu / Rasaya Marimuthu and Elangkeeran Sabapathy - Marimuthu, Rasaya; Sabapathy, Elangkeeran (2005)
The deficiency in the English language among graduates churned out by local universities including UiTM is at a worrisome level. Handicap in the English language can be attributed to several factors. Very often, the utilization of ineffective study strategies can contribute towards this problem in language learning, just like in any other areas of learning. Studies have shown that the proper application of cognitive strategies aid in the identification and retention of ideas of a learning unit. This study was undertaken to prove the above possibility. The researchers were particularly interested in finding out how the use of one particular cognitive strategy (concept mapping) could enhance the performance of students in reading comprehension lessons. Since the language learning realm can be very wide, the focus was narrowed down to the skill of identifying main and supporting ideas in reading comprehension passages. The experimental design comprised two groups (Experimental and Control) of the DCS Part 3 students taking the Mainstream English II course. There was a significant improvement in the achievement level of the experimental group in the posttest conducted after the treatment process. Similarly, the experimental group, having gone through the treatment phase, performed significantly better than the control group in the given test. These findings, supported by findings of other researches elsewhere lend a hand to the popular notion that the use of appropriate cognitive strategies can contribute towards improved reading comprehension skills. It is hoped that the finding will also encourage language instructors and others to train their charges to employ such strategies in their learning as a step towards nurturing autonomous learners.